2022
DOI: 10.1093/cid/ciac831
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Tuberculous Meningitis

Abstract: Background Cognitive impairment is reported as a common complication in adult tuberculous meningitis (TBM), yet few studies have systematically assessed the frequency and nature of impairment. Moreover, the impact of impairment on functioning and medication adherence is not described. Methods A cognitive test battery (10 measures assessing 7 cognitive domains) was administered to 34 participants with HIV-associated TBM 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Fourth, our study was focused on the complications caused by stroke in TBM patients. Previous studies have shown that other TBM complications, such as myelitis ( 22 ), vision impairment ( 23 ), cognitive dysfunction ( 24 ), and seizure ( 25 ), similarly affect patients' quality of life. Long-term follow-up and neurological monitoring may be necessary for TBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our study was focused on the complications caused by stroke in TBM patients. Previous studies have shown that other TBM complications, such as myelitis ( 22 ), vision impairment ( 23 ), cognitive dysfunction ( 24 ), and seizure ( 25 ), similarly affect patients' quality of life. Long-term follow-up and neurological monitoring may be necessary for TBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…showed that microRNA-124 modulates the proliferation of Mycobacterium by inhibiting the signal transducer and activator of transcription 3 signaling pathway ( 72 ). Although microglia play an immune supervisor role in the CNS, the long-lasting activation of microglia induces hyper-neuroinflammation, which may induce neurotoxicity and impair the cognitive ability in TB patients ( 73 ). As the main component of myeloid cells, microglia infiltration reflects the brain inflammatory activation status in TBM ( 74 ).…”
Section: Biological Roles Of Microglia In Tbmmentioning
confidence: 99%
“…A retrospective study showed that 144 of 559 (25.8%) patients admitted with TBM had cerebral infarcts diagnosed with brain imaging, with three-quarters of them being acute or subacute [ 30 ]. In addition, hyponatremia and tuberculous brain abscesses are common macroscopic manifestations of TBM, and cognitive impairment occurs in approximately half of the patients with TBM concurrently infected with HIV, which cannot be ascribed to limited focal structural deficits such as tuberculomas [ 6 ]. These characteristics can exist separately or in combination and may not be detected radiographically until the disease has progressed ( Fig.…”
Section: Pathogenesis Of Tbmmentioning
confidence: 99%
“…Much of the damage caused by TBM results from host-derived inflammatory responses, frequently due to non-productive neuroinflammation, in which microglia play a major initiating role [ 5 ]. Although microglia serve as immune supervisors in the central nervous system (CNS), their prolonged activation causes hyper neuroinflammation, which has the potential to be neurotoxic and impair the cognition of patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%